2022
DOI: 10.1097/md.0000000000030711
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the life expectancy in malignant pleural mesothelioma: Our 10 years of studies and experience

Abstract: Malignant pleural mesothelioma (MPM) is an aggressive tumor with a poor prognosis. In our study, we aimed to investigate the specific clinical, laboratory, and radiological features of the tumor and the prognostic effect of SUVmax (maximum standardized uptake values) according to PET/CT (positron emission tomography). Demographic, therapeutic, clinical, and survival information of patients diagnosed with histologically-validated pleural mesothelioma in our hospital between January 2010 to December 2019 will be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
1
1
0
Order By: Relevance
“…Our multivariate analysis showed that the prognosis of elderly patients with mesothelioma was worse than that of young patients. This was consistent with the results of many previous studies [ 35 , 47 ], which was easy to understand. Elderly patients generally had more basic diseases, poor pulmonary function, and limited access to treatment.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our multivariate analysis showed that the prognosis of elderly patients with mesothelioma was worse than that of young patients. This was consistent with the results of many previous studies [ 35 , 47 ], which was easy to understand. Elderly patients generally had more basic diseases, poor pulmonary function, and limited access to treatment.…”
Section: Discussionsupporting
confidence: 93%
“…This also potentially suggests the reason for the low proportion of men in this study. However, in some studies, the proportion of women is as high as 40 − 50% [ 34 , 35 ]. This suggests that the gender proportion of MPM varies in different regions.…”
Section: Discussionmentioning
confidence: 99%